Classification and mapping of marine-island landscape in Nam Yet Island, Truong Sa Islands, Vietnam - Nguyen Dang, Hoi; Ngo Trung, Dung; Kuznetsov , A.N.; Vu Le, Phuong (Vietnam Journal of Earth Sciences, 2022)
Classification and mapping of marine-island landscapes according to an integrated approach not only clarifies the structure and division of natural units of the sea areas but also creates a basis for the orientation of natural resource management resources, environmental protection, and conservation of marine-island biodiversity. The principles of marine-island landscape mapping are to define terminology and establish a classification system based on taxonomy and criteria. This article represents the establishment of marine-island landscape mapping of Nam Yet Island and adjacent water (scaled at 1:10000) through comprehensive work, including marine-island landscape classification, applied GIS - remote sensing, and field investigation in the two years of 2020-2021. Accordingly, the landscape classification system of the Nam Yet Island area includes 1 system, 1 subsystem, 4 classes, 6 subclasses, 10 types, 29 kinds, and 34 forms of landscape (of which 4 island forms and 30 marine forms). The units of the marine-island landscape fully express the natural components, anthropogenic factors, and biotic and abiotic factors in their relationship and interaction with each other. Depending on each corresponding level, the detailed level of components and landscape elements is shown, in which components and biological factors are studied and analyzed most fully. The research results have clarified the characteristics and the law of differentiation of the marine-island landscape in Nam Yet Island, contributing to supplementing knowledge about Truong Sa Islands of Vietnam, which is a scientific basis for resource management and biodiversity conservation, protecting the marine environment, and at the same time supplementing the theoretical basis for the study of the tropical monsoon tropical island and marine landscape, which has not yet been studied in Vietnam.